2004
DOI: 10.2337/diacare.27.6.1381
|View full text |Cite
|
Sign up to set email alerts
|

Results of Blood Inflammatory Markers Are Associated More Strongly With Toe-Brachial Index Than With Ankle-Brachial Index in Patients With Type 2 Diabetes

Abstract: TOSHIHIKO INUKAI, MD 1OBJECTIVE -Three blood markers of inflammation (high-sensitivity C-reactive protein [hsCRP], interleukin [IL]-6, and fibrinogen) were compared with markers of atherosclerotic cardiovascular disease (CVD) (history of stroke or cardiac ischemia and measured toe-brachial index [TBI]) to determine whether inflammatory markers are associated with atherosclerosis in patients with type 2 diabetes.RESEARCH DESIGN AND METHODS -Of 103 patients with type 2 diabetes, 26 had CVD. TBI was plethysmograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
2
22
0
1
Order By: Relevance
“…This study found no correlation between serum lipid and ABI values, which is consistent with findings for studies of a hemodialysis population, [18] diabetic population, [20,21] and general population. [14] However, Newman et al demonstrated that hyperlipidemia was associated with low ABI value in an elderly population (77±6 years).…”
Section: Ankle-brachial Indexsupporting
confidence: 91%
“…This study found no correlation between serum lipid and ABI values, which is consistent with findings for studies of a hemodialysis population, [18] diabetic population, [20,21] and general population. [14] However, Newman et al demonstrated that hyperlipidemia was associated with low ABI value in an elderly population (77±6 years).…”
Section: Ankle-brachial Indexsupporting
confidence: 91%
“…Yoshimasa Aso et al, [10] who studied the association of TBI and ABI with multiple blood markers of inflammation such as hsCRP, IL-6, and fibrinogen, found a significant negative correlation of TBI but not ABI with the serum hsCRP. They suggested that the falsely high ABI (>1.3) values which were due to a medial arterial calcification may account for the absence of a significant correlation between hsCRP and the ABI in the diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…These blockages restrict the blood circulation, mainly in the arteries, leading to blockages in the kidneys, stomach, arms, legs and feet [8,9]. Since ABI is said to be a marker of the atherosclerotic burden, the low ABI in Type 2 DM often indicates a significant atherosclerosis in the vascular beds [10]. Thus, ABI can be considered as a suitable method for assessing PVD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheen et al 11 reported that low eGFR was a major determinant of low TBI, as well as low ABI; however, eGFR was associated more strongly with TBI than with ABI in patients with type 2 diabetes. Moreover, Aso et al 16 reported that serum inflammatory marker, including C-reactive protein, showed significant negative correlation with TBI but not with ABI.…”
Section: Discussionmentioning
confidence: 99%